Health professionals' licensing: the practice and its predictors among health professional hiring bodies in Ethiopia - Endalkachew Tsedal Alemneh; Biruk Hailu Tesfaye; Eshetu Cherinet Teka; Firew Ayalew; Ermias Gebreyohannes Wolde; Wondimu Daniel Ashena; Tewodros Abebaw Melese; Fikadie Dagnew Biset; Bezawit Worku Degefu; Bethlehem Bizuayew Kebede; Yohannes Molla Asemu; Meron Yakob Gebreyes; et al. (BMC, 2022)
Abstract Background Evidence suggests that not all human resource departments have hired their facility staff based on federal licensing standards, with some hiring without an active license. This is common in some, if not all, parts of the country. The paucity of healthcare experts, high turnover rates, employee burnout, and challenges in training and development issues were all key recruiting challenges globally. Objective To assess the practice of health professionals' licensing and its predictors among hiring bodies in Ethiopia, March 24/2021-May 23/2021. Methods A cross-sectional study was conducted in privately and publicly funded health facilities throughout Ethiopia. For each region, a stratified sampling strategy was utilized, followed by a simple random sampling method. Documents from the recruiting bodies for health professionals were reviewed. A pretested structured questionnaire and document review tool were used to extract data confidentially. A descriptive analysis of the basic hiring body characteristics was conducted. Hiring body characteristics were analyzed in bivariate and multivariate logistic regression to identify factors associated with best health professionals licensing practice. Data management and analysis were conducted with Epi-Data version 4.4.3.1 and SPSS version 23, respectively. Results The analysis included 365 hiring bodies and 4991 files of health professionals (1581 from private and 3410 from public health organizations). Out of 365 hiring bodies studied, 66.3% practiced health professional licensing. A total of 1645 (33%) of the 4991 professionals whose files were reviewed were found to be working without any professional license at all. Furthermore, about 2733 (55%) have an active professional license, and about 603 (12%) were found to work with an expired license. Being a private facility (adjustedOR = 21.6; 95% CI = 8.85-52.55), obtaining supervision from a higher organ (adjustedOR = 19.7; 95%CI: 2.3-169.1), and conducting an internal audit (adjustedOR = 2.7; 95% CI: 1.15-6.34) were predictors of good licensing practice. Conclusions The licensing of health practitioners was poorly practiced in Ethiopia as compared to the expected proclamation of the country. A system for detecting fake licenses and controlling revoked licenses does not exist in all regions of the country.